Examples, Exemplars, Principles. - Bittner, Rüdiger (Topoi: An International Review of Philosophy, 2025)
We find out what is right to do, both when the problem is a technical and when it is a moral one, by heeding what we or others did in similar situations and how we or they then fared. This is to say, we find out what is right to do by means of examples. This claim is contested by exemplarists who hold that it is specifically by way of admiring exemplary human beings and actions that we come to see what is morally right to do. It is also contested by those who hold that it is only through principles that we learn what is morally right in the case at hand. As regards exemplarism, however, it is doubtful that our feeling of admiration is a reliable guide in moral matters. Indeed, there is reason to think that admiration with its eye on what is higher than common humanity rests on unjustifiable assumptions. The friends of principles in turn need to explain why it should be important, not just to do what is right in the case at hand, but in so doing to be following a moral principle. This idea probably derives from a questionable Jewish, Christian and Stoic heritage. In sum, there is reason to hold on to the initial claim that through examples we learn what is right to do.